A pre-lithiation silicon-based carbon composite material and its preparation method and application
By using Li-MOF and polymer chain/silica composite powder in lithium-ion batteries, the problem of interface film instability caused by volume expansion of silicon anode material during lithiation is solved, and carbon material and silicon are realized Uniform bonding of materials and efficient lithium storage.
Patent Information
- Application Number
- CN202411676330.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-22
AI Technical Summary
In existing lithium-ion batteries, the volume expansion of the silicon negative electrode material during the lithiation process leads to instability of the solid electrolyte interface film, affecting the cycle stability and energy density of the battery.
By compositeing the Li-MOF powder with the polymer chain/silica composite powder and carbonizing at high temperatures, a prelithiated silicon-based carbon composite material with a uniform bond between the carbon material and the silicon material is formed.
The bonding strength and bond uniformity between carbon materials and silicon materials are improved, the cycle stability and lithium storage capacity of the battery negative electrode materials are enhanced, and the first-effect performance of lithium-ion batteries is improved.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery preparation, and specifically relates to a pre-lithiation silicon-based carbon composite material and a preparation method and application thereof. Background Art
[0002] As a key area of energy storage battery development, lithium-ion batteries have always attracted much attention, especially in the field of power batteries. Among many excellent high-energy lithium-ion battery negative electrodes, the theoretical specific capacity of silicon negative electrode materials is more than 10 times that of graphite negative electrodes. It is believed that it can replace graphite as the next generation of high-energy density negative electrode materials for lithium-ion batteries. In addition, silicon has the advantages of high natural abundance and environmental friendliness. However, the huge volume expansion of silicon during the lithiation process causes the solid electrolyte interface film on the silicon surface to become unstable, which will repeatedly break and regenerate, resulting in continuous consumption of electrolyte and the formation of thick and uneven solid electrolyte interface film, making the first coulomb efficiency of silicon negative electrode very low. In order to solve this problem, the current method is mainly to pre-lithiate the silicon negative electrode to compensate for the active lithium consumed by the formation of the solid electrolyte interface film during the first charging process. By compounding silicon materials with carbon materials to obtain silicon-based carbon composite materials, the volume change during the lithium insertion and extraction process is reduced, and the loss of electrolyte is reduced, thereby improving the energy density of the battery. Therefore, silicon-carbon-based composite materials are widely studied and applied as lithium-ion battery electrode materials.
[0003] Patent CN112125294A discloses a coal-based silicon-carbon composite negative electrode material and its preparation method, which uses anthracite as a carbon source, low-temperature carbonization to obtain amorphous porous carbon, and diatomaceous earth as a silicon source. The porous structure of diatomaceous earth itself can reserve expansion space, effectively improving the expansion problem of silicon-based negative electrodes. The prepared coal-based silicon-carbon composite negative electrode material is pre-lithiated to improve the cycle stability of the negative electrode material; however, this scheme prepares the amorphous porous carbon and silicon-based materials separately and sinters them for composite. The dispersion degree of the silicon-based material in the amorphous porous carbon is low, and the initial performance of the negative electrode material is less improved.
[0004] Patent CN116062730A discloses a preparation method of a pre-lithiated silicon-based composite material, a pre-lithiated silicon-based composite material and its application, wherein a Li2CO3-coated lithium rod is used as a working electrode, a silicon-based composite material is deposited on the surface of the working electrode by an electrochemical deposition method, and the silicon-based composite material is subjected to high-temperature carbonization sintering to obtain a pre-lithiated silicon-based composite material; however, vapor deposition will only be deposited on the surface of the silicon-based material, and the uniformity of bonding with the silicon-based material is insufficient. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of insufficient uniformity and strength of the combination of carbon materials and silicon materials, so as to improve the initial performance of carbon materials in lithium batteries, and to provide a pre-lithiation silicon-based carbon composite material and its preparation method and application.
[0006] The present invention prepares polymer chain / silicon dioxide composite powder by depositing nano-silicon dioxide particles with aminated polymer chains, and composites the prepared polymer chain / silicon dioxide composite powder with Li-MOF powder in ethanol by adsorption and then carbonizes at high temperature, so that the ligands and polymer chains in the Li-MOF powder are carbonized on the surface of silicon dioxide, thereby obtaining a pre-lithiation silicon-based carbon composite material in which carbon material and silicon material are evenly combined.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A method for preparing a pre-lithiated silicon-based carbon composite material comprises the following steps:
[0009] Step 1: Mix tetramethoxysilane and aminated polymer solution in a reaction kettle, stir at 20-30° C. for 30-40 min, add anhydrous ethanol to dilute and then centrifuge, collect the precipitate, vacuum dry at 40-50° C., and crush into micron-sized powder using a ball mill to obtain a polymer chain / silicon dioxide composite powder.
[0010] Step 2: Ultrasonic disperse the Li-MOF powder in anhydrous ethanol, add the polymer chain / silicon dioxide composite powder, heat at 40-50°C and stir, stop heating when the anhydrous ethanol is about to evaporate completely, transfer to a vacuum drying chamber and dry at 40-50°C to constant weight to obtain the powder to be carbonized.
[0011] Step 3: Place the powder to be carbonized in a muffle furnace and heat it to 950-1000° C. under nitrogen protection for 2-3 hours, and obtain a pre-lithiated silicon-based carbon composite material after cooling.
[0012] Furthermore, in step 1, the dosage ratio of tetramethoxysilane, aminated polymer solution and anhydrous ethanol is 12-15 mL: 25-30 mL: 30-40 mL.
[0013] Further, the aminated polymer solution is prepared by the following steps:
[0014] The polymer solution is mixed with triethylamine in a reaction kettle, and reacted at 25-30° C. for 60-72 hours to obtain an aminated polymer solution.
[0015] Furthermore, the usage ratio of the polymer solution to triethylamine is 50-60 mL:4-5 mL.
[0016] Further, the polymer solution is prepared by the following steps:
[0017] In a reaction kettle, add 2-(dimethylamino)ethyl methacrylate to tetrahydrofuran and mix, add a dilute hydrochloric acid aqueous solution with a pH value of 2-3 to the reaction kettle, then add 2-(diisopropylamino)ethyl methacrylate, stir and mix evenly, then add azobisisobutyronitrile, heat to 40-50°C and react for 16-18h, then adjust the pH value to 7-7.5 with a 1M sodium hydroxide aqueous solution to obtain a polymer solution.
[0018] Furthermore, the usage ratio of 2-(dimethylamino)ethyl methacrylate, tetrahydrofuran, dilute hydrochloric acid aqueous solution, 2-(diisopropylamino)ethyl methacrylate and azobisisobutyronitrile is 6-8 g: 180-200 mL: 400-600 mL: 3-4 g: 15-20 mg.
[0019] Furthermore, in step 2, the usage ratio of Li-MOF powder, anhydrous ethanol and polymer chain / silicon dioxide composite powder is 15-20 g: 100-120 mL: 10-25 g.
[0020] Further, Li-MOF powder is prepared by the following steps:
[0021] In a reactor, lithium sulfate was dissolved in deionized water, and then hexadecyltrimethylammonium bromide was dissolved in 70wt% ethanol aqueous solution and slowly added into the reactor, and stirred at 40-50°C at 400-500rpm for 30-40min, isophthalic acid was added into the reactor, and the temperature was raised to 65-75°C for reaction for 12-16h, the precipitate was collected and washed with deionized water, and vacuum dried at 80-85°C for 20-24h to obtain Li-MOF powder.
[0022] Furthermore, the usage ratio of lithium sulfate, deionized water, hexadecyltrimethylammonium bromide, ethanol aqueous solution and isophthalic acid is 18-20 g: 1.8-2 L: 10-12 g: 500-600 mL: 10-12 g.
[0023] Beneficial effects of the present invention:
[0024] (1) The preparation method of the present invention comprises the following steps: compounding Li-MOF powder with polymer chain / silicon dioxide composite powder so that the surface of nano-silicon dioxide is wrapped by polymer chains and Li-MOF. The silicon-based carbon composite material formed after carbonization has high bonding strength between the silicon-based material and the carbon material, and the silicon-based material is evenly dispersed in the carbon material. The high temperature during carbonization causes the Li element in the Li-MOF to sublime, and the gaseous Li element reacts more fully with the silicon dioxide for thermal reduction, so that the generated silicon-based carbon composite material is pre-lithiated, thereby obtaining a pre-lithiated silicon-based carbon composite material with good bonding uniformity between the carbon material and the silicon material and high strength.
[0025] (2) The present invention uses triethylamine to aminate the polymer chain. Triethylamine has good solubility in the polymer solution and the degree of amination of the polymer chain is more uniform, thereby increasing the nitrogen content in the polymer chain and improving the conductivity and lithium storage capacity of the carbonized silicon-based carbon composite material, thereby improving the initial performance of the pre-lithiation silicon-based carbon composite material in the application of lithium-ion battery negative electrode materials. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1: A method for preparing a pre-lithiated silicon-based carbon composite material, comprising the following steps:
[0028] Step 1: Add 6 g of 2-(dimethylamino)ethyl methacrylate to 180 mL of tetrahydrofuran in a reactor and mix. Add 400 mL of a dilute hydrochloric acid solution with a pH value of 2 to the reactor, then add 3 g of 2-(diisopropylamino)ethyl methacrylate, stir and mix evenly, then add 15 mg of azobisisobutyronitrile, heat to 40°C and react for 16 hours, then adjust the pH value to 7 with a 1 M sodium hydroxide solution to obtain a polymer solution.
[0029] Step 2: Mix 250 mL of the polymer solution with 20 mL of triethylamine in a reaction kettle and react at 25° C. for 60 h to obtain an aminated polymer solution.
[0030] Step 3: Mix 120 mL of tetramethoxysilane and 250 mL of aminated polymer solution in a reactor, stir at 20°C for 30 min, add 300 mL of anhydrous ethanol to dilute, centrifuge at 14000 rpm, collect the precipitate, dry it in vacuum at 40°C, and crush it into micron-sized powder using a ball mill to obtain a polymer chain / silicon dioxide composite powder.
[0031] Step 4: Dissolve 18 g of lithium sulfate in 1.8 L of deionized water in a reactor, then dissolve 10 g of hexadecyltrimethylammonium bromide in 500 mL of 70 wt% ethanol aqueous solution and slowly add the mixture to the reactor. Stir at 400 rpm for 30 min at 40 °C, add 10 g of isophthalic acid to the reactor, heat to 65 °C and react for 12 h, collect the precipitate, wash with deionized water, and vacuum dry at 80 °C for 20 h to obtain Li-MOF powder.
[0032] Step 5: Ultrasonic disperse 15 g of Li-MOF powder in 100 mL of anhydrous ethanol, add 10 g of polymer chain / silicon dioxide composite powder, heat and stir at 40 ° C, stop heating when the anhydrous ethanol is about to evaporate completely, transfer to a vacuum drying chamber and dry at 40 ° C to constant weight to obtain the powder to be carbonized.
[0033] Step 6: Place the powder to be carbonized in a muffle furnace and heat to 950° C. under nitrogen protection for 2 hours, and obtain a pre-lithiated silicon-based carbon composite material after cooling.
[0034] Embodiment 2: A method for preparing a pre-lithiated silicon-based carbon composite material, comprising the following steps:
[0035] Step 1: Add 7 g of 2-(dimethylamino)ethyl methacrylate to 190 mL of tetrahydrofuran in a reactor and mix. Add 500 mL of a dilute hydrochloric acid solution with a pH value of 2.5 to the reactor, then add 3.5 g of 2-(diisopropylamino)ethyl methacrylate, stir and mix well, then add 17 mg of azobisisobutyronitrile, heat to 45 ° C and react for 17 hours, then adjust the pH value to 7.3 with a 1 M sodium hydroxide aqueous solution to obtain a polymer solution.
[0036] Step 2: Mix 275 mL of the polymer solution with 22.5 mL of triethylamine in a reaction kettle, and react at 27.5° C. for 66 h to obtain an aminated polymer solution.
[0037] Step 3: Mix 135 mL of tetramethoxysilane and 275 mL of aminated polymer solution in a reactor, stir at 25°C for 35 min, add 350 mL of anhydrous ethanol to dilute, centrifuge at 15,000 rpm, collect the precipitate, dry in vacuo at 45°C, and crush into micron-sized powder using a ball mill to obtain a polymer chain / silicon dioxide composite powder.
[0038] Step 4: Dissolve 19 g of lithium sulfate in 1.9 L of deionized water in a reactor, then dissolve 11 g of hexadecyltrimethylammonium bromide in 550 mL of 70 wt% ethanol aqueous solution and slowly add the solution to the reactor. Stir at 45 °C and 450 rpm for 35 min. Add 11 g of isophthalic acid to the reactor, heat to 70 °C and react for 14 h. Collect the precipitate, wash with deionized water, and vacuum dry at 82 °C for 22 h to obtain Li-MOF powder.
[0039] Step 5: Ultrasonic disperse 17.5 g of Li-MOF powder in 110 mL of anhydrous ethanol, add 17.5 g of polymer chain / silicon dioxide composite powder, heat at 45 ° C and stir, stop heating when the anhydrous ethanol is about to evaporate completely, transfer to a vacuum drying chamber and dry at 45 ° C to constant weight to obtain the powder to be carbonized.
[0040] Step 6: Place the powder to be carbonized in a muffle furnace and heat to 975° C. under nitrogen protection for 2.5 hours, and obtain a pre-lithiated silicon-based carbon composite material after cooling.
[0041] Embodiment 3: A method for preparing a pre-lithiated silicon-based carbon composite material, comprising the following steps:
[0042] Step 1: In a reactor, add 8 g of 2-(dimethylamino)ethyl methacrylate to 200 mL of tetrahydrofuran and mix. Add 600 mL of a dilute hydrochloric acid solution with a pH value of 3 to the reactor, then add 4 g of 2-(diisopropylamino)ethyl methacrylate, stir and mix well, then add 20 mg of azobisisobutyronitrile, heat to 50°C and react for 18 hours, then adjust the pH value to 7.5 with a 1 M sodium hydroxide solution to obtain a polymer solution.
[0043] After dispersing 2-(dimethylamino)ethyl methacrylate in tetrahydrofuran, the pH value of the solution is adjusted, and 2-(diisopropylamino)ethyl methacrylate and an initiator azobisisobutyronitrile are added to dissolve and disperse the polymer in the solution. Cross-linking is completed during the dispersion process to form a hydrophilic-hydrophobic polymer. After the polymerization is completed, the hydrophobicity of the polymer is increased and dissolved by raising the pH value to form a polymer chain.
[0044] Step 2: Mix 300 mL of the polymer solution with 25 mL of triethylamine in a reaction kettle and react at 30° C. for 72 h to obtain an aminated polymer solution.
[0045] Triethylamine is weakly alkaline and highly soluble in water. It can be well dispersed in the polymer solution, and the polymer chains in the polymer solution are modified by amination, thereby increasing the amino content on the surface of the polymer chains, thereby increasing the N element content on the surface of the polymer chains.
[0046] Step 3: Mix 150 mL of tetramethoxysilane and 300 mL of aminated polymer solution in a reaction kettle, stir at 30°C for 40 min, add 400 mL of anhydrous ethanol to dilute, centrifuge at 16000 rpm, collect the precipitate, dry it in vacuum at 50°C, and crush it into micron-sized powder using a ball mill to obtain a polymer chain / silicon dioxide composite powder.
[0047] Step 4: Dissolve 20 g of lithium sulfate in 2 L of deionized water in a reactor, then dissolve 12 g of hexadecyltrimethylammonium bromide in 600 mL of 70 wt% ethanol aqueous solution and slowly add the mixture to the reactor. Stir at 50 °C at 500 rpm for 40 min, add 12 g of isophthalic acid to the reactor, heat to 75 °C and react for 16 h, collect the precipitate, wash with deionized water, and vacuum dry at 85 °C for 24 h to obtain Li-MOF powder.
[0048] Step 5: Ultrasonic disperse 20 g of Li-MOF powder in 120 mL of anhydrous ethanol, add 25 g of polymer chain / silicon dioxide composite powder, heat at 50 ° C and stir, stop heating when the anhydrous ethanol is about to evaporate completely, transfer to a vacuum drying chamber and dry at 50 ° C to constant weight to obtain the powder to be carbonized.
[0049] Step 6: Place the powder to be carbonized in a muffle furnace and heat to 1000° C. under nitrogen protection for reaction for 3 hours, and obtain a pre-lithiated silicon-based carbon composite material after cooling.
[0050] Li-MOF and polymer chain / silicon dioxide composite powder are dispersed in anhydrous ethanol, and the adsorption capacity of Li-MOF is used to adsorb Li-MOF on the surface of the polymer chain / silicon dioxide composite powder. The composite powder is heated under nitrogen protection, and the polymer chain and the ligand of Li-MOF are carbonized to form a carbon layer coated on the surface of nano-silicon dioxide, thereby improving the bonding strength and bonding uniformity between the carbon material and the silicon material, and the N element on the surface of the polymer chain is doped in the generated carbon layer, thereby improving the electrical conductivity and lithium storage capacity. At the same time, the metallic lithium in Li-MOF sublimates at high temperature, and the sublimated lithium metal contacts the nano-silicon dioxide more evenly, and the sublimated lithium metal contacts the nano-silicon dioxide to produce a thermal reduction reaction, thereby preparing a SiOx-based carbon-coated material, i.e., a silicon-based carbon composite material, and the silicon-based carbon composite material is pre-lithiated, thereby improving the cycle stability of the silicon-based carbon composite material as a negative electrode material for lithium-ion batteries.
[0051] Comparative Example 1: The difference from Example 1 is that nano-silicon dioxide powder is used to replace the polymer chain / silicon dioxide composite powder to obtain the powder to be carbonized, and then the powder to be carbonized is first kept at 350°C for 2 hours, and then the temperature is raised to 850°C. After keeping it for 2 hours, a mixture of natural gas and hydrogen is introduced for gas phase coating, and the reaction is carried out for 1 hour to obtain a pre-lithiation silicon-based carbon composite material.
[0052] Comparative Example 2: The difference from Example 1 is that the aminated polymer solution is replaced by a polymer solution.
[0053] Comparative Example 3: Li-MOF was replaced by lithium powder, and the lithium powder was physically mixed with the polymer chain / silicon dioxide composite powder to obtain the powder to be carbonized, and the powder to be carbonized was heated to 700° C. under nitrogen protection to obtain a pre-lithiated silicon-based carbon composite material.
[0054] The sources of some reagents in the embodiments and comparative examples are as follows:
[0055] 2-(Dimethylamino)ethyl methacrylate, tetrahydrofuran, 2-(diisopropylamino)ethyl methacrylate, lithium sulfate, and isophthalic acid were purchased from Sigma-Aldrich.
[0056] Azobisisobutyronitrile was purchased from Zibo Tongyizhai Chemical Co., Ltd.
[0057] Triethylamine, tetramethoxysilane, and hexadecyltrimethylammonium bromide were purchased from MacLean Reagent Co., Ltd.
[0058] The pre-lithiation silicon-based carbon composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used to prepare the negative electrode of lithium batteries for performance testing. Sodium carboxymethyl cellulose and styrene-butadiene rubber were used as binders. The pre-lithiation silicon-based carbon composite materials, binders and acetylene black conductive agents were mixed in a ratio of 7:2:1 and then coated on copper foil to prepare circular pole pieces. The pole piece diameter was 12 mm. The weight of the pole piece was weighed and recorded. The pole piece was used as the working electrode, the metal lithium sheet was used as the counter electrode, the diaphragm was a Celgard 2500 lithium battery diaphragm, the electrolyte was a 1M lithium hexafluorophosphate mixed solution, the solvent of the mixed solution was an equal volume mixture of ethylene carbonate and diethyl carbonate, and 5 wt% of fluoroethylene carbonate was added to assemble into a CR2032 button cell. The battery was subjected to constant current charge and discharge tests, and the measured voltage range was 0.005-2V. The first cycle was at 0.02C (1C=4200mAg -1 ) was activated at a low current density, and then a long cycle performance test was performed at a current density of 0.1C. The results are shown in Table 1:
[0059] Table 1
[0060] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 First discharge capacity (mAh / g) 1532.8 1548.2 1559.4 1195.3 1421.7 1369.6 First efficiency (%) 93.5 93.7 94.1 87.2 93.6 90.3 100 cycles capacity retention rate (%) 94.2 94.4 94.5 85.1 88.3 89.6
[0061] As can be seen from Table 1, the pre-lithiation silicon-based carbon composite materials obtained in Examples 1 to 3 of the present invention have high capacity and high initial efficiency, and the capacity retention rate is high after 100 cycles, indicating that the silicon-based and carbon-based materials of the present invention have high bonding strength, uniform bonding degree, and good pre-lithiation performance; in Comparative Example 1, nano-silicon dioxide powder is directly used to composite with Li-MOF powder, and then gas-phase coating is performed. Since nano-silicon dioxide is easy to agglomerate, the gas-phase coating has low coating property for nano-silicon dioxide, and it is easy to coat the agglomerated nano-silicon dioxide, and the obtained silicon-based carbon composite material has poor electrical properties; in Comparative Example 2, the nitrogen content in the silicon-based carbon composite material is reduced by amination modification of the polymer solution, and the first discharge capacity is low, and the capacity decays rapidly after 100 cycles; in Comparative Example 3, lithium powder is mixed with polymer chain / silicon dioxide composite powder for pre-lithiation, but since silicon dioxide is deposited on the surface of the polymer chain and does not completely coat silicon dioxide, the bonding strength between the carbon material and the silicon material of the obtained silicon-based carbon composite material is low, so the tested electrical properties are poor.
[0062] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a pre-lithiated silicon-based carbon composite material, characterized in that: The steps include: Step 1: Mix tetramethoxysilane and aminated polymer solution in a reaction kettle, stir at 20-30° C. for 30-40 min, add anhydrous ethanol to dilute and then centrifuge, collect the precipitate, dry in vacuum at 40-50° C., and grind into micron-sized powder using a ball mill to obtain polymer chain / silicon dioxide composite powder; Step 2: Ultrasonically disperse the Li-MOF powder in anhydrous ethanol, add the polymer chain / silicon dioxide composite powder, heat at 40-50° C. and stir, stop heating when the anhydrous ethanol is about to evaporate completely, transfer to a vacuum drying chamber and dry at 40-50° C. to constant weight to obtain a powder to be carbonized; Step 3: Place the powder to be carbonized in a muffle furnace and heat it to 950-1000° C. under nitrogen protection for reaction for 2-3 hours, and obtain a pre-lithiated silicon-based carbon composite material after cooling.
2. The method for preparing a pre-lithiated silicon-based carbon composite material according to claim 1, characterized in that: The usage ratio of tetramethoxysilane, aminated polymer solution and anhydrous ethanol in step 1 is 12-15 mL: 25-30 mL: 30-40 mL.
3. The method for preparing a pre-lithiated silicon-based carbon composite material according to claim 2, characterized in that: The aminated polymer solution is prepared by the following steps: Mixing the polymer solution with triethylamine in a reaction kettle, and reacting at 25-30° C. for 60-72 hours to obtain an aminated polymer solution; The usage ratio of the polymer solution to triethylamine is 50-60 mL:4-5 mL.
4. The method for preparing a pre-lithiated silicon-based carbon composite material according to claim 3, characterized in that: The polymer solution is prepared by the following steps: In a reaction kettle, add 2-(dimethylamino)ethyl methacrylate to tetrahydrofuran and mix, add a dilute hydrochloric acid aqueous solution with a pH value of 2-3 to the reaction kettle, then add 2-(diisopropylamino)ethyl methacrylate, stir and mix evenly, then add azobisisobutyronitrile, heat to 40-50°C and react for 16-18h, then adjust the pH value to 7-7.5 with a 1M sodium hydroxide aqueous solution to obtain a polymer solution.
5. The method for preparing a pre-lithiated silicon-based carbon composite material according to claim 4, characterized in that: The usage ratio of 2-(dimethylamino)ethyl methacrylate, tetrahydrofuran, dilute hydrochloric acid aqueous solution, 2-(diisopropylamino)ethyl methacrylate and azobisisobutyronitrile is 6-8g:180-200mL:400-600mL:3-4g:15-20mg.
6. The method for preparing a pre-lithiated silicon-based carbon composite material according to claim 1, characterized in that: The usage ratio of the Li-MOF powder, anhydrous ethanol and polymer chain / silicon dioxide composite powder in step 2 is 15-20 g: 100-120 mL: 10-25 g.
7. The method for preparing a pre-lithiated silicon-based carbon composite material according to claim 6, characterized in that: The Li-MOF powder is prepared by the following steps: In a reactor, lithium sulfate was dissolved in deionized water, and then hexadecyltrimethylammonium bromide was dissolved in 70wt% ethanol aqueous solution and slowly added into the reactor, and stirred at 40-50°C at 400-500rpm for 30-40min, isophthalic acid was added into the reactor, and the temperature was raised to 65-75°C for reaction for 12-16h, the precipitate was collected and washed with deionized water, and vacuum dried at 80-85°C for 20-24h to obtain Li-MOF powder.
8. The method for preparing a pre-lithiated silicon-based carbon composite material according to claim 7, characterized in that: The usage ratio of the lithium sulfate, deionized water, hexadecyltrimethylammonium bromide, ethanol aqueous solution and isophthalic acid is 18-20g:1.8-2L:10-12g:500-600mL:10-12g.
9. A pre-lithiation silicon-based carbon composite material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.
10. Use of the pre-lithiated silicon-based carbon composite material according to claim 9 in a negative electrode material for a lithium-ion battery.
Citation Information
Patent Citations
Coal-based silicon-carbon composite negative electrode material and preparation method thereof
CN112125294A
Novel silicon-carbon composite negative electrode material and preparation method thereof
CN111180717A
Composite binder of lithium ion battery silicon-carbon negative electrode material and preparation method and application thereof
CN113363487A